Comparative effects of high oleic acid vs high mixed saturated fatty acid obesogenic diets upon PUFA metabolism in mice. (April 2017) - Picklo, Sr., Matthew J.; Idso, Joseph; Seeger, Drew R.; Aukema, Harold M.; Murphy, Eric J.
Abstract: Emerging evidence indicates that the fatty acid composition of obesogenic diets influences physiologic outcomes. There are scant data regarding how the content of non-essential fatty acids like monounsaturated fatty acids (MUFA) and saturated fatty acids (SFAs) impact the metabolism of polyunsaturated fatty acids (PUFAs). In this work, we tested the hypothesis that obesogenic diets enriched in oleic acid (OA; 18:1n-9) reduce polyunsaturated fatty acid (PUFA) levels vs an obesogenic diet enriched in SFAs. Adult male mice were fed for eight weeks either (1) a control 16% fat energy (en) diet with 5.7% en OA and 4.4% en SFA, (2) a 50% fat en diet with 33% en OA and 9.9% en SFA, or (3) a 50% en diet with a high SFA diet with 33% en SFA and 9.1% en OA. Dietary levels and intake of linoleic acid (LA; 18:2n-6) and α-linolenic acid (ALA; 18:3n-3) were constant between the experimental groups. Several peripheral organs (liver, heart, kidney, and adipose) were analyzed for lipid composition and oxylipin analysis was performed for liver and adipose. Our data demonstrate that a high OA diet reduced tissue content of LA and ALA (≥30%) in phospholipid and neutral lipid fractions, reduced the content of some LA-derived and ALA-derived oxylipins in liver and adipose, and conversely, elevated hepatic content of PGF2α . In all tissues examined, except for adipose, levels of arachidonic acid (ARA; 20:4n-6) and docosahexaenoic acid (DHA; 22:6n-3) were either elevated or unaffected by the obesogenic diets. Our data indicate that the non-essential fatty content of obesogenic diets impacts PUFA content in peripheral tissues and influences the levels of bioactive oxylipins. Highlights: Monounsaturated vs saturated fatty acids impact tissue polyunsaturated fatty acids. A high-fat oleic reduced the tissue content of linoleic and alpha-linolenic acids. A high-fat oleic diet reduced n-3 and n-6 oxylipins in liver and adipose. High-fat diets increased n-3 and n-6 long-chain PUFA in many tissues except adipose.